2015
DOI: 10.1016/j.ijwd.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of outcome measures for atopic dermatitis in patients with pigmented skin: A grey area

Abstract: BackgroundOutcome measures for atopic dermatitis (AD) patients with pigmented skin have neither been developed nor validated.ObjectiveTo compare the reliability and validity of four common AD outcome measures in patients with various levels of skin darkness.MethodThe inter- and intra-rater reliability and construct validity of the EASI (Eczema Area and Severity Index), objective-SCORing Atopic Dermatitis (oSCORAD), Three Items Severity index (TIS) and Six Areas, Six Sites Atopic Dermatitis (SASSAD) were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
(28 reference statements)
1
27
2
Order By: Relevance
“…As opposed to findings from a previous similar study performed using full‐body photographs of patients with AD, in patients with SOC, erythema perception was not found to be a contributor to the inter‐rater variability in the EASI or oSCORAD. Surprisingly, in lighter‐skinned patients, the EASI score's erythema component reduced its inter‐rater variability (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As opposed to findings from a previous similar study performed using full‐body photographs of patients with AD, in patients with SOC, erythema perception was not found to be a contributor to the inter‐rater variability in the EASI or oSCORAD. Surprisingly, in lighter‐skinned patients, the EASI score's erythema component reduced its inter‐rater variability (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…The reliabilities of EASI and oSCORAD were shown to be much higher in our study than in a previous study performed using photographs, where the reliabilities of all clinician‐rated AD outcome measures were poor in patients with SOC, and were either fair or good in light‐skinned patients . Another problem with photographs is assessing the area involved, as all areas of the skin and folds are harder to appreciate than with patients examined in person.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…53 This is contrary to previous studies which demonstrated poor reliability in pigmented skin. 54 Despite the strong performance of EASI in trials, it is more cumbersome to conduct than the Physician Global Assessment (PGA) in clinical practice. PGA, also known as the Investigator Global Assessment (IGA), is considered easier to conduct and more clinically relevant compared to other investigator assessments.…”
Section: Physician Assessment Toolsmentioning
confidence: 99%
“…Although the morphology of AD varies according to Fitzpatrick skin phototype, an accurate diagnosis of AD can still be made using the Hanifin‐Rajka criteria or the American Academy of Dermatology consensus criteria, although investigators should be made aware that patients with darker skin (higher Fitzpatrick skin phototype) often have less visibly apparent erythema, more lichenification, greater follicular prominence, and more areas of dyspigmentation. Data are conflicting with regard to the performance of current scoring systems (including EASI and SCORAD) for patients with highly pigmented skin …”
Section: Development Programmentioning
confidence: 99%